Development of SCAR Marker for Detection of Sex Expression in Papaya (Carica papaya L.) from Several Genetic Backgrounds - , Sobir; Sriani Sujiprihati; Evalina C. Pandia (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
Papaya plants are hermaphrodite, pistillate, or staminate. Sex inheritance in papaya is determined by a single gene locus with three alleles of M which is dominant for maleness, MH for hermaphrodites and m which is recessive for femaleness. Only fruits from hermaphrodite plants are marketed since they have the necessary commercial characteristics, i.e., they are pear-shaped and have thicker flesh and a smaller internal cavity. Increased papaya yield has been limited mainly by the ratio of female to hermaphrodite (1: 2) plants normally occurring in orchards. This ratio causes great losses to papaya producers. Identification of seedlings sex during nursery stage is of prime iportance. In order to obtain simple DNA markers to identify sex expression in papaya, five SCAR markers of 20-21 primers were utilized. Examination of these markers into 24 genotypes of papaya from 12 populations of different genetic background revealed that pair of primer PKBT-5 had successfully differentiated male and hermaphrodite plants from female plants. Hence, PKBT-5 pair of primer can be utilized as DNA marker for sex expression character identification in papayas.   Key words: Papaya, sex expression, SCAR marker